On the Internationalization of Corporate Boards - Lars Oxelheim; Aleksandra Gregori; Trond Randøy; Steen Thomsen (Research Institute of Industrial Economics (IFN), 2013)
Despite the global reach of their commercial activities, many multinational firms have proved slow in internationalizing their boards of directors. Based on a panel study of the internationalization of the boards of 347 non-financial firms from the Nordic countries, we find a higher fraction of international board membership in firms with more foreign sales, in firms with more foreign ownership and in firms whose shares are traded on foreign (mostly European) stock exchanges. Moreover, we find international directors and national directors with international experience complementary. The first-mentioned group is found to serve a monitoring role, related to financial internationalization of the firm, whereas the latter category fills an advisory role related to commercial internationalization. Hence, different types of firm internationalization commercial versus financial might call for different types of board internationalization.
Keywords: F23; G30; G34; L22; M16; 330; Internationalization; International directors; International board experience; Board composition; Nomination committee; Corporate governance